Biotic Elicitors in Adventitious and Hairy Root Cultures: A Review from 2010 to 2022 - Miguel Angel Alcalde; Edgar Perez-Matas; Ainoa Escrich; Rosa M. Cusido; Javier Palazon; Mercedes Bonfill (Molecules, 2022)
One of the aims of plant in vitro culture is to produce secondary plant metabolites using plant cells and organ cultures, such as cell suspensions, adventitious, and hairy roots (among others). In cases where the biosynthesis of a compound in the plant is restricted to a specific organ, unorganized systems, such as plant cell cultures, are sometimes unsuitable for biosynthesis. Then, its production is based on the establishment of organ cultures such as roots or aerial shoots. To increase the production in these biotechnological systems, elicitors have been used for years as a useful tool since they activate secondary biosynthetic pathways that control the flow of carbon to obtain different plant compounds. One important biotechnological system for the production of plant secondary metabolites or phytochemicals is root culture. Plant roots have a very active metabolism and can biosynthesize a large number of secondary compounds in an exclusive way. Some of these compounds, such as tropane alkaloids, ajmalicine, ginsenosides, etc., can also be biosynthesized in undifferentiated systems, such as cell cultures. In some cases, cell differentiation and organ formation is necessary to produce the bioactive compounds. This review analyses the biotic elicitors most frequently used in adventitious and hairy root cultures from 2010 to 2022, focusing on the plant species, the target secondary metabolite, the elicitor and its concentration, and the yield/productivity of the target compounds obtained. With this overview, it may be easier to work with elicitors in in vitro root cultures and help understand why some are more effective than others.